Energy technology perspectives 2015: mobilising innovation to accelerate climate action (Paris, 2015)
"As climate negotiators work towards a deal that would limit the increase in global temperatures, interest is growing in the essential role technology innovation can and must play in enabling the transition to a low-carbon energy system. Indeed, recent success stories clearly indicate that there is significant and untapped potential for accelerating innovation in clean technologies if proper policy frameworks are in place. In an especially timely analysis, the 2015 edition of Energy Technology Perspectives (ETP 2015) examines innovation in the energy technology sector and seeks to increase confidence in the feasibility of achieving short- and long-term climate change mitigation targets through effective research, development, demonstration and deployment (RDD&D). ETP 2015 identifies regulatory strategies and co operative frameworks to advance innovation in areas like variable renewables, carbon capture and storage, and energy-intensive industrial sectors. The report also shows how emerging economies, and China in particular, can foster a low-carbon transition through innovation in energy technologies and policy. Finally, ETP 2015 features the IEA annual Tracking Clean Energy Progress report, which this year shows that efforts to decarbonise the global energy sector are lagging further behind. By setting out pathways to a sustainable energy future and by incorporating detailed and transparent quantitative modelling analysis and well-rounded commentary, ETP 2015 and its series of related publications are required reading for experts in the energy field, policy makers and heads of governments, as well as business leaders and investors. "